2017
DOI: 10.1103/physrevlett.119.032001
|View full text |Cite
|
Sign up to set email alerts
|

J/ψ Production and Polarization within a Jet

Abstract: We study the production and polarization of J/ψ mesons within a jet in proton-proton collisions at the LHC. We define the J/ψ-jet fragmentation function as a ratio of differential jet cross sections with and without the reconstructed J/ψ in the jet. We demonstrate that this is a very useful observable to help explore the J/ψ production mechanism, and to differentiate between different NRQCD global fits based on inclusive J/ψ cross sections. Furthermore, we propose to measure the polarization of J/ψ mesons insi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…A number of other jet observables that account for transverse momentum dependence have recently been considered. The main focus has been on the transverse momentum of hadrons fragmenting in jets, in both inclusive [4] and semi-inclusive [5,6] processes. In the same context, refs.…”
Section: Contentsmentioning
confidence: 99%
“…A number of other jet observables that account for transverse momentum dependence have recently been considered. The main focus has been on the transverse momentum of hadrons fragmenting in jets, in both inclusive [4] and semi-inclusive [5,6] processes. In the same context, refs.…”
Section: Contentsmentioning
confidence: 99%
“…The functions G c (z, p T , R, τ, µ) are the semi-inclusive jet mass functions (siJMFs), which describe how a parton c initiates the signal jet that carries a momentum fraction z of that parton, and at the same time the jet mass τ is observed. Following earlier work [52,[56][57][58][59], the siJMFs are defined at the operator level as follows…”
Section: First Step: Hard Collinear Factorizationmentioning
confidence: 99%
“…The factorization analysis in Refs. [11,12] showed that the standard TMD fragmentation functions enter when the transverse momentum of a hadron is measured with respect to the standard jet axis (SJA). If instead the Winner-Take-All (WTA) axis [13,14] is used, a new and rather different TMD is obtained: it is insensitive to soft radiation and has a DGLAP-like evolution equation [15].…”
mentioning
confidence: 99%